Security and Data Storage Aspect in Cloud Computing - Deshpande, Prachi S.; Sharma, Subhash C.; Peddoju, Sateesh K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book analyses the various security threats in cloud computing. A host-based IDS (HIDS) using signature verification is developed and implemented for the concerned security issues. Further, owing to the vulnerability of distributed denial of service (DDoS) attacks in cloud computing, a network based IDS (NIDS) is developed and implemented against such attacks. The performance of these IDS is verified in the Cloud scenario as well against the standard data set. Finally, a simple data storage and security model is developed and implemented for the Cloud computing scenario. The contents of this book will be of interest to researchers and professionals alike.
1. Introduction -- 2. Host-based Intrusion Detection System -- 3. Network-based Intrusion Detection System -- 4. Data Security and Storage Module in Cloud -- 5. Conclusions and Research Direction.
Keywords: Telecommunication; Data protection; Big data; Communications Engineering, Networks; Data and Information Security; Big Data